Measuring mechanical anisotropy of the cornea with Brillouin microscopy - Amira M. Eltony; Peng Shao; Seok-Hyun Yun (Nature Communications, 2022)
Here, Brillouin optical microscopy noninvasively visualizes microscale anisotropy of the porcine cornea owing to its lamellar fiber structure and quantifies the longitudinal moduli of the bulk tissue. Anisotropy is also detected in angle-resolved measurement of the human cornea in vivo.